PERAN BAWASLU DALAM UPAYA PENCEGAHAN PELANGGARAN PILKADA TAHUN 2024 DI KABUPATEN CIREBON - Nou’im Hayat; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The prevention of violations in general and regional elections carried out by Bawaslu (the Election Supervisory Body) constitutes an integral component of electoral law enforcement, complementing the imposition of sanctions against violations committed by election participants. Such preventive efforts are crucial to ensuring electoral integrity, safeguarding the constitutional rights of citizens, and realizing electoral justice. Law No. 7 of 2017 on General Elections grants Bawaslu both the mandate and the authority to undertake preventive measures in electoral law enforcement, particularly through proactive interventions at every stage of the electoral process. Meanwhile, Law No. 1 of 2016 on Regional Head Elections sets forth the mechanisms governing the conduct of local elections. Bawaslu’s preventive measures are diverse in scope, encompassing the mitigation of electoral vulnerabilities, the issuance of early warnings through advisory letters, the implementation of close supervision across all electoral stages, and, importantly, the mobilization of public participation in monitoring the electoral process. This study seeks to examine the legal framework regulating the prevention of electoral violations as well as its practical implementation during the 2024 Regional Head Election (Pilkada) in Cirebon Regency. The research employs a normative juridical method, supported by empirical data, to analyze both the regulatory provisions and their application in practice.